Answered

If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f circle g) (x)? (3x + 2)(x 2 + 1) 3x 2 + 1 + 2 (3x + 2)2 + 1 3(x 2 + 1) + 2

Answer :

altavistard

Answer:

(f circle g) (x) = 3x^2 + 5

Step-by-step explanation:

To find (f circle g)(x), we substitute function g(x) for x in f(x) = 3x + 2:

(f circle g) (x) = 3(x^2 + 1) + 2, or

                         3x^2 + 3 + 2, or

(f circle g) (x) = 3x^2 + 5

Answer:

(f circle g) (x) = 3x^2 + 5

Step-by-step explanation:

Other Questions